Women's Historical Studies: Perspectives on Islamic Development, Traces of Women's Thought in Historical Studies - Abdul Azis; Husaini Husaini; Amiruddin Amiruddin; Sanusi Sanusi; Nurasiah Nurasiah; Zulfan Zulfan; Teuku Muhammad Husni; Rizal Fahmi; Yusrijal Abdar (Jurnal Ragam Pengabdian, 2026)
This article discusses the position of women in the development of Islam by tracing the traces of thought evolving in the history of Islam, from the early period of Islam, the classical era, to contemporary thought in Indonesia. Islam brings significant changes to the dignity of women by granting rights, respect, and broader opportunities in various aspects of life. In the course of history, diverse interpretations have emerged that sometimes limit and sometimes reinforce the roles of women in both domestic and public spaces. Women are not only understood as companions in the family, but also as seekers of knowledge, narrators of hadith, ulama, educators, leaders, and important actors in social-religious life. The thoughts of figures such as M. Quraish Shihab and Amina Wadud show that the understanding of Islamic teachings continues to evolve with changing times, especially in the issues of education, gender relations, and the authority of interpretation. Therefore, the position of women in Islam can be understood as part of the dynamic history of thought that continues to develop, diversify, and be open to a more just and inclusive interpretation.